Molecular biology of the cell - Sergey Dolomatov; Elizaveta Ageeva; Walery Zukow (Kazimierz Wielki University, 2022)
The book is intended for students studying medical and biological specialties.     CHAPTER I. EPIGENETICS INTRODUCTION The science of epigenetics looks at the mechanisms of molecular modifications of histones and DNA that can regulate gene activity without affecting the nucleotide sequences in the DNA molecule. Recognized epigenetic regulators are DNA methylation, post-translational modifications of histones, and non-coding RNAs (nkRNAs). One of the most important differences between eukaryotic cells and prokaryotes is the presence of a complex nucleo-protein chromatin complex in eukaryotes. It is in this form that the DNA molecule is stored in our cells. On the one hand, the complex structural organization of chromatin provides a compact arrangement of DNA in the cell nucleus. On the other hand, chromatin is directly involved in the process of regulating gene expression. At the same time, the nucleosome depicted in Fig. 1 (a structural and functional unit of chromatin) is considered as a key component in the processes of regulating gene expression.   The nucleus of the nucleosome is 8 histone proteins (octamers). The nucleus of the nucleosome consists of two copies of each of the histone proteins H2A, H2B, H3 and H4. The DNA chain, which includes 147 nucleotides, folds 1.65 times around the octamer of histones. The nucleosomes are arranged as a linear array along the DNA molecule in the form of "beads on a string". The linker section of DNA connecting adjacent nucleosomes (transcriptionally inactive) is sealed with H1-histone protein. The length of the linker section is 30 nm. Moreover, the site of the beginning of transcription is usually located inside the nucleosome. Consequently, the nucleosome serves as a gene repressor, preventing the initiation of transcription. That is, chromatin provides a total repression of genes. In contrast, transcription becomes possible as a result of chromatin remodeling factors that enable the "dismantling" of nucleosomes or otherwise alter their structure and organization. Thus, the repression (inactivation) of genes begins with wrapping the DNA molecule around the histones in the nucleosome, and the liberation of genes from repression (activation) involves freeing DNA from binding to histone proteins and unfolding DNA by chromatin remodeling factors (Lorch Y., Kornberg R. D., 2017). Thanks to this mechanism, selective expression of only those genes that are needed at a given time by the cell or tissue is possible. It should be emphasized that nucleosome repression extends not only to transcription, but also to most other biological processes associated with the DNA molecule, such as replication, mitotic division, repair of double-strand breaks, and maintenance of telomeres. Thus, epigenetic mechanisms control various physiological and pathological processes by regulating the expression of the corresponding genes by changing the availability of epigenetic control systems to chromatin. The scope of application of epigenetic research methods is rapidly expanding. Currently, we are witnessing the active introduction of epigenetic approaches in the field of practical medicine aimed at diagnosing and treating dangerous human diseases.                 CHAPTER II. TRANSCRIPTION FACTORS INTRODUCTION For the first time, the existence of transcription factors was revealed on the basis of a discovery that made it possible to establish in vitro purified RNA polymerase-II can initiate transcription on the DNA template in the presence of a cell extract (Weil P.  A. et al., 1979). Further research aimed at the fractionation and identification of the general transcription factors (GTF) required to initiate transcription in vitro has identified similar factors in rats, Drosophila, and yeast and substantiated the assumption that GTFs are indeed "common" factors necessary for the expression of genes transcribed by RNA polymerase II.  is highly conserved in a number of eukaryotic organisms (Matsui T.  et al., 1980). We only mention RNA polymerase II because only this type of enzyme has the ability to synthesize mRNA. Whereas RNA polymerase I is responsible for the synthesis of pro-rRNA, and RNA polymerase III is responsible for the synthesis of tRNA and other non-coding cell RNAs.  Meanwhile, the regulation of transcription in eukaryotes is quite complex, since it depends on chromatin remodeling complexes (Burns L. G., Peterson C. L., 1997) and covalent modification of histone proteins (Natsume-Kitatani Y., Mamitsuka H., 2016). In transcription initiation, the immediate target of GTF is a well-defined promo zone of a structural gene.  In the structure of the promotra of eukaryotes, the main elements and regulatory elements can be distinguished. The main elements of the promotra (bark promoter, see Fig. 2.1) can be attributed to the site for assembling the transcription initiation complex (PIC), including the TATA sequence located above from the transcription start site (TSS ), and an initiating sequence (Inr) covering the start site. Promoters may include a TATA unit, an initiator sequence (Inr), or both (Hampsey M., 1998).  A third major element, the downstream promoter element (DPE), was originally described in Drosophila and is located about 30 p.p. below TSS. The DPE promoter element appears to function in conjunction with the Inr element as a binding site for the transcription factor TFIID on non-TATA promoters.   According to current research, the cellular (main) promoters of multicellular organisms that control the initiation of transcription by RNA polymerase II may contain short sequences of nucleotides called cow promoter elements (motifs) (e.g., the TATA block, the initiator (Inr), and the lower element of the cow promoter (DPE)) that recruit RNA polymerase II through a common transcription initiation mechanism (Dreos R.  et al., 2021). The authors report that the classes of Promoters of Inr+DPE are not only present in the genome of Drosophila and humans and are structurally similar to each other, but may also be common to different species of multicellular organisms.   The most studied element of the cow promoter is the TATA box, but the TATA box is found only in about 10-20% of multicellular cortical promoters. Therefore, along with the TATA sequence, it is necessary to name other possible key DNA sequences known as cortical promoter elements, which include: BRE, MTE, TST and DPE sequences. The two BRE (TFIIB recognition element) motifs are located either above (BREu) or below (BREd) elements of the TATA box. It should be emphasized that TBP, TATA box, and BRE demonstrate high levels of conservatism in the range from archaebacteria to humans (Kadonaga J. T., 2012). In doing so, BREu as well as BREd have both positive and negative effects on transcription activity. The downstream core promoter element (DPE) was detected in the analysis of non-TATA gene promoters in Drosophila. The MTE element (motif ten element), which is located directly in front of the DPE, was identified as an overrepresented sequence of a cow promoter called "motif 10" and then discovered,  that it is a functional element of a cow promoter. The MTE and DPE motifs exhibit high conservatism in the range from Drosophila to humans, and both motifs appear to be directly recognized by the subunits of the main transcription factor TFIID, TAF proteins that resemble histone proteins in structure. In turn, the TCT sequence regulates the transcription of ribosomal protein genes in Drosophila and humans. Although there are no universal cortical promoter elements that are present in all promoters, the concept of a cow promoter of nuclear RNA polymerase II can be defined as a minimum stretch of DNA that is sufficient to accurately initiate transcription by RNA polymerase II (Kadonaga J. T., 2012;  Haberle V., Stark A., 2018). It should be noted that the results of modern research will constantly supplement the list of all new components of the cow promoter, for example, DNA-replicatedrelated element (DRE), Ohler 1,6 and 7 motifs (Danino Y. M. et al., 2015;  Haberle V., Stark A., 2018). According to the authors, the bark promoter may be transformed in the course of evolution. Due to this, gene expression levels can be modulated by the composition of cow promoter elements.